Antiepileptic Drugs in Clinical Development: Differentiate or Die? - Zaccara, Gaetano; Schmidt, D. (Current Pharmaceutical Design, 2017)
Background: Animal models when carefully selected, designed and conducted, are important parts of any translational drug development strategy. However, research of new compounds for patients with drugresistant epilepsies is still based on animal experiments, mostly in rodents, which are far from being a model of chronic human epilepsy and have failed to differentiate the efficacy of new compounds versus standard drug treatment. Objective: The objective was identification and description of compounds in clinical development in 2016. Method: Search was conducted from the website of the U.S. National Institutes of Health and from literature. Results: Identified compounds have been divided in two groups: 1) compounds initially developed for the treatment of diseases other than epilepsy: biperiden, bumetanide, everolimus, fenfluramine, melatonin, minocycline, verapamil. 2) Compounds specifically developed for the treatment of epilepsy: allopregnanolone, cannabidiol, cannabidivarin, ganaxolone, nalutozan, PF-06372865, UCB0942, and cenobamate. Everolimus, and perhaps, fenfluramine are effective in specific epileptic diseases and may be considered as true disease modifying antiepileptic drugs. These are tuberous sclerosis complex for everolimus and Dravet syndrome for fenfluramine. With the exception of a few other compounds such as cannabinidiol, cannabidivarin and minocycline, the vast majority of other compounds had mechanisms of action which are similar to the mechanism of action of the anti-seizure drugs already in the market. Conclusion: Substantial improvements in the efficacy, specifically as pharmacological treatment of drug-resistant epilepsy is regarded, are not expected. New drugs should be developed to specifically target the biochemical alteration which characterizes the underlying disease and also include targets that contribute to epileptogenesis in relevant epilepsy models.
Keywords: allopregnanolone